Creativity and intelligence in children with and without developmental dyslexia - Alves, Rauni Jandé Roama; Nakano, Tatiana de Cássia (Paidéia (Ribeirão Preto), 2014)
This study aimed to verify if the creativity of children with Developmental Dyslexia (CG; n = 13) differs from children without difficulties in reading and writing (NG; n = 13). Furthermore, we sought to verify how creativity could be related to intelligence. The Raven Colored Progressive Matrices Test and the Child Figural Creativity Test were applied in both groups. High correlations were found between intelligence and creativity in both groups, and variable correlations for the same type of analysis were found in the literature. There were no significant intergroup differences for creativity, although the NG had a higher overall average in creativity and the CG, the highest averages in most evaluated creative characteristics. The possible involvement of psychological/neuropsychological constructs with creativity, such as spatial processing and emotion, was discussed.